PENGUKURAN E-LEARNING READINESS PADA MAHASISWA TEKNIK UNIVERSITAS TELKOM - Litasari W Suwarsono (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This paper explores engineering student’s readiness towards e-learning in Telkom University Bandung that developed e-learning system to complement its method. Some studies had indicated predictor behaviors for effective e-learning process were self-directed learning, technical readiness and comfort with non-face to face communication (Warner et al , 1998; Piskurich, 2003; Smith, 2005; Hung et al., 2010). Data gathered from 388 Telkom University engineering students (57% from sophomore year and 43% from junior year). Self-assessment method had been used to predict student readiness toward e-learning. Research found that Telkom University engineering student’s level of readiness was on ready with development, with technical readiness factor as the highest level and self-directed learning readiness as the lowest. The level of grade had no statistical differences on self-directed learning readiness and technical readiness factor but it had on comfort with non-face to face communication.